Does fairness matter? Consumers' perception of fairness in the agro-food chain - Del Prete, Margherita; Samoggia, Antonella (Frontiers in Sustainable Food Systems, 2023)
Introduction Defining ‘fairness’ in the agro-food sector is a challenging task. There is no single definition of fairness and the literature does not provide a complete conceptualization from the consumer's point of view. The current research seeks to explore the consumers' interest in fairness and ethics in the agro-food chain by exploring (i) a comprehensive theoretical framework to conceptualize fairness from a consumer perspective, and (ii) the consumers' perceived importance of different food attributes as fairness-related aspects. Method Literature review and focus groups allowed for the creation of the final survey to be submitted to consumers. 529 valid responses from a predominantly Italian female sample were collected. Data were elaborated with Exploratory Factor Analysis and ANOVA test. Results The research identified five dimensions of fairness: Fair price, environment, networking, short chain, and working condition. Also, it emerged that age influences consumers' perceived importance of products with fair attributes. Discussion This research contributes to the development of a fairer and more sustainable food system by identifying perceptions of agro-food chain fairness and establishing a link with food shopping intentions. The research provides companies with suggestions on how to expand sales by reaching a greater number of consumers.